2023
DOI: 10.1182/bloodadvances.2022007802
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism prophylaxis in sickle cell disease: a multicenter cohort study of adolescent inpatients

Abstract: Patients with sickle cell disease (SCD) are predisposed to a hypercoagulable state. Despite the increased risk of venous thromboembolism in the SCD population, there is limited evidence available to guide thromboprophylaxis (TP) practices in these patients. This study aimed to assess the use of pharmacologic and nonpharmacologic TP in adolescent patients with SCD using the Pediatric Health Information System (PHIS). We hypothesized that TP was increasingly used in hospitalized adolescent patients with SCD. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Several studies have explored potential risk factors contributing to VTE in SCD. A comprehensive study in 2020, which included 1193 pediatric and adult SCD patients, identified factors such as a lower estimated glomerular filtration rate, hydroxyurea use, HbSS/Sβ0 genotype, elevated white blood cell (WBC) counts, and Hb level as independent risk factors associated with VTE [32]. A 2021 study from Oman on 102 SCA patients (68 with VTE and 34 controls) highlighted high WBC count, serum lactate dehydrogenase (LDH), bilirubin, C-reactive protein (CRP), and low hemoglobin and hemoglobin F levels as significant VTE risk factors [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored potential risk factors contributing to VTE in SCD. A comprehensive study in 2020, which included 1193 pediatric and adult SCD patients, identified factors such as a lower estimated glomerular filtration rate, hydroxyurea use, HbSS/Sβ0 genotype, elevated white blood cell (WBC) counts, and Hb level as independent risk factors associated with VTE [32]. A 2021 study from Oman on 102 SCA patients (68 with VTE and 34 controls) highlighted high WBC count, serum lactate dehydrogenase (LDH), bilirubin, C-reactive protein (CRP), and low hemoglobin and hemoglobin F levels as significant VTE risk factors [6].…”
Section: Discussionmentioning
confidence: 99%
“…Using the slicer-dicer tool in our institutional electronic health care record (EPIC Systems, Verona, WI) we found a staggeringly high percentage of patients admitted for sickle cell crisis with a pre-admission use of anticoagulants (see Figure 1). In fact, the trend in the use of pharmacologic thromboprophylaxis in hospitalized adolescent patients with SCC steadily increased in the last decade owing to the increased risk of VTE (6,7). Multiple sites of pain a patient with SCC can present with might be another factor that limits the effective use of RA techniques in these patients (8).…”
Section: Tomentioning
confidence: 99%
“…In fact, the trend in the use of pharmacologic thromboprophylaxis in hospitalized adolescent patients with SCC steadily increased in the last decade, owing to the increased risk of VTE. 6,7 Often, SCC presents withmultiple non-contiguous sites of pain which might be another factor that limits the effective use of RA techniques in these patients. 8 To add to this complexity, patients, especially children with SCD are at increased risk of bloodstream infections 9 where the prevalence of bacteremia in febrile patients with SCD can be as high as 1.9%.…”
mentioning
confidence: 99%